Play Therapy and the Therapeutic Use of Story - Carlson, Roxanne; Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
Children who develop behavioural problems are often living with severe emotional pain. Children can achieve personal growth, healing and alleviation of their emotional pain through treatment that allows the processing of traumatic events and experiences in a medium that is both natural and comfortable for them. Play therapy and the therapeutic use of stories allow children to distance themselves from painful themes and deal with them symbolically. This article explores the healing process of a 6-year-old boy whose chaotic family lifestyle and structured school environment presented more anxiety than he could cope with effectively.